2003
DOI: 10.1074/jbc.m300195200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of the 20 S Proteasome of Trypanosoma brucei

Abstract: We describe here biochemical characterization of the 20 S proteasome from the parasitic protozoan Trypanosoma brucei. Similar to the mammalian proteasome, the T. brucei proteasome is made up of seven ␣-and seven ␤-subunits. Of the seven ␤-type subunits, five contain pro-sequences that are proteolytically removed during assembly, and three of them are predicted to be catalytic based on primary sequence. Affinity labeling studies revealed that, unlike the mammalian proteasome where three ␤-subunits were labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…1c): Mtb20SWT, Mtb20SOG, Rhod20S, and bov20S. Substrate concentrations were kept at 10 M, equal to or a few-fold lower than the values of K m (10 -200 M) previously reported for tri/tetrapeptide substrates (24,30). Under these conditions, reaction rates likely reflected the specific activity (k cat /K m ) in the absence of substrate saturation effects.…”
Section: Ac-p3p2p1-amc Library and Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…1c): Mtb20SWT, Mtb20SOG, Rhod20S, and bov20S. Substrate concentrations were kept at 10 M, equal to or a few-fold lower than the values of K m (10 -200 M) previously reported for tri/tetrapeptide substrates (24,30). Under these conditions, reaction rates likely reflected the specific activity (k cat /K m ) in the absence of substrate saturation effects.…”
Section: Ac-p3p2p1-amc Library and Assaymentioning
confidence: 99%
“…Studies of substrate specificities have been reported for proteasomes of human (22,23) and another eukaryote, Trypanosoma brucei (24), using positional scanning substrate or inhibitor libraries. The positional scanning libraries were usually constructed as 20 pools/position (P1, P2, P3, and P4), each of which contained large numbers of peptides fixed at a single residue and otherwise variant.…”
mentioning
confidence: 99%
“…High-resolution crystal structures have demonstrated that the PA28 homolog, PA26, induces a conformational change in the N-termini of 20S ␣-subunits that opens the entrance of the catalytic chamber (Whitby et al, 2000;Forster et al, 2005). PA28 (PA26) also alters the proteolytic properties of 20S and/or 19S-20S proteasomes by modifying the pattern, but not the overall size of cleaved products (Harris et al, 2001;Li et al, 2001;Cascio et al, 2002;Wang et al, 2003). PA28␣␤ subunits are particularly abundant in immune tissues and are coordinately regulated by IFN␥ together with ␤1i, ␤2i, and ␤5i subunits of the immunoproteasome, ER peptide transporters (TAP1, TAP2), and MHC class I molecules (Frü h and Yang, 1999;Rechsteiner et al, 2000;Kloetzel and Ossendorp, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…ABPs targeting serine proteases (81,82), cysteine proteases (85)(86)(87)(88), threonine proteases (89,90), aspartyl proteases (91), and metalloproteases (92,93) have been developed. Metallo-and aspartic proteases pose difficulty in the design and application of ABPs due to the absence of a covalent acyl intermediate in the catalytic mechanism.…”
Section: Activity-based Probesmentioning
confidence: 99%